Financial relaxation of Islamic rural banks and private schools resilience during COVID-19 - Riduwan Riduwan; Zalik Nuryana; Rofiul Wahyudi; Suyadi Suyadi; Lina Handayani (Institute of Advanced Engineering and Science, 2024)
The pandemic of COVID-19 has increased tensions between Islamic rural banks and private schools. Many parents lose their jobs and are thus unable to pay their children’s school tuition. Private schools, on the other hand, are heavily reliant on tuition and bank financing. As a result, student enrollment falls, school finances suffer a deficit, many parents and students lose trust in the school, and some students may wish to drop out. This research aimed to investigate the effectiveness of financial relaxation on schools’ resilience. It was qualitative research with a case study approach focusing on the causal relationship of an Islamic rural banks with a private school affected by the COVID-19 pandemic in Muhammadiyah 1 Yogyakarta Vocational High School and Islamic rural banks’ Bangun Drajat Warga (BDW). The research finding reveals that BDW Islamic rural banks has implemented financing relaxation three times to ease the school’s burden and it has resulted in an improvement in the school’s resilience by as much as 33%. Besides, due to the high ideological commitment and adaptability of Muhammadiyah 1 Yogyakarta Vocational High School as well as the success of gaining parents’ trust regarding online teaching and learning, there has been an increase in the school tuition by as much as 80%. Although though the COVID-19 epidemic is coming to an end, it is still important to study the financial flexibility of Islamic rural banks and private schools in similar crises in the past to better prepare for the future.